Heiress in red silk - Hunter, Madeline (Hunter, Madeline. Duke's heiress., 2021)
Inheriting a fortune and a new business, Rosamund Jameson matches wits with her new partner, Kevin Radnor, who proposes a marriage of convenience to get her the social status she needs and guarantees him the silent partner he wants — a plan that soon goes awry.